Manajemen Gizi Mikro dan Dampak Kesehatan pada Lansia: Literature Review: Management of Micro Nutrition and Health Impacts on the Elderly: Literature Review - Vina Firmanty Mustofa; Budi Prasetyo; Diah Indriani; Nur Anisah Rahmawati (Universitas Airlangga, 2023)
Background: The population of elderly worldwide is increasing unnoticed, including in Indonesia. The world's population is aging, and many elderly people experience age-related malnutrition, including deficiencies in some micronutrients. Malnutrition in the elderly is a serious condition when the nutritional needs of the elderly do not match their food intake. Objectives: This systematic review broadly reviews various micronutrient problems and health impacts on the elderly in several countries. Methods: Systematic review following PRISMA guidelines. Several databases have been accessed; the PubMed, Google Scholar, and ScienceDirect databases use a combination of MESH terms and relevant keywords. The inclusion criteria applied were studies written in English, evaluating relevant topics, providing full text, and published studies from 2017-2022 Discussion: Many disorders associated with aging are related to micronutrient deficiencies. Various factors cause micronutrient deficiencies in the elderly, but inadequate food intake is the main factor influencing this deficiency. Nutritional deficiencies experienced by the elderly are closely related to decreased immune function. The results of this review explain that the elderly experience malnutrition due to a lack of the following nutrients: vitamin D, folic acid, calcium, and vitamin B12. Conclusions: Micronutrient deficiency in the elderly causes a variety of comorbidities that reduce the elderly's quality of life in old age, such as heart disease, high blood pressure, diabetes, electrolyte imbalance, dementia, and anemia. The development of food-based dietary guidelines and health promotion regarding elderly nutrition in several countries should be recommended, and it is also necessary to update national food intake references.